(NmAN@N)QÆNA DOROGA (B((NzA m(B. (NwÆNGRANOWSXKIM(B) /s)E - (NwASKAN(B, (NwASILX wASILXOWI^(B.s ((N~ERN)QÆWCÆ (B:s)E (NzOLOT)QÆ LITAWRI(B,s)E, 2016)
(N~ERGOWA ZB)QÆRKA ^ERNÆWECXKOGO POETA w(B. (NwASKANA WIJ[LA U WIDAWNICTWÆ (B"(NzOLOTÆ LITAWRI(B" (NU SERÆÇ (B"(NrODINA(B". (NkNIGA PRISWQ^ENA (B80-(NRÆ^^@ WÆD dNQ NARODVENNQ mIKOLI wÆNGRANOWSXKOGO(B. (NtUT WMÆ]ENÆ WÆR[Æ TA PÆSNÆ PRISWQ^ENÆ WIDATNOMU UKRAÇNSXKOMU POETU(B-(N[ÆSTDESQTNIKU(B. (NbUDE CÆKAWO@ WSÆM(B, (NHTO CÆKAWITXSQ SU^ASNO@ POEZÆÃ@(B.s)E
(NdO (B80-(NR)QÆ^^Q WÆD DNQ NARODVENNQ mIKOLI wÆNGRANOWSXKOGOs)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (NuKRA)QÇNSXKAs)E -- (NpOEZ)QÆQ(B.s)E; (NmUZIKAs -- (NwOKALXNA MUZIKAs -- (NuKRA)QÇNA(B.s)E; (NmUZIKAs -- (NmUZI^N)QÆ VANRIs)E -- (NwOKALXN)QÆ MUZI^NÆ VANRIs)E -- (Np)QÆSNÆs)E -- (NuKRA)QÇNA(B.s)E; (N~ERN)QÆWECXKIJ AWTOR(B.s)E